2006
DOI: 10.1007/s10531-005-0600-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Epilithic Diatoms in Response to Environmental Conditions in an Urban Tropical Stream, Central Kenya

Abstract: Use of diatoms in monitoring water quality is well acknowledged in developed countries, but only recently has the assessment started gaining importance in developing countries. Diatoms can be obtained from natural and artificial substrates. Appreciating the differences and similarities of diatom assemblages on both substrates may contribute to a better understanding and standardization particularly during monitoring of water quality. During this study we assessed diatom assemblages, biodiversity and trophic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 44 publications
8
33
0
6
Order By: Relevance
“…These events caused an increased conductivity, and/or Cl -and/or nutrient concentration in almost all sampling sites. The results supported our third hypothesis, that evenness of diatom assemblages decreases with increasing conductivity and/or nutrient content (NH 4 + , PO 4 3-), according to ZALAT (2002), NDIRITU et al (2006) and STENGER-KOVÁCS et al (2013). Confi rming our fi ndings, they observed a decreasing diversity in diatom assemblages parallel to increasing salinity/conductivity, and/or nutrient (especially phosphate) contents.…”
Section: Changes In Evennesssupporting
confidence: 88%
“…These events caused an increased conductivity, and/or Cl -and/or nutrient concentration in almost all sampling sites. The results supported our third hypothesis, that evenness of diatom assemblages decreases with increasing conductivity and/or nutrient content (NH 4 + , PO 4 3-), according to ZALAT (2002), NDIRITU et al (2006) and STENGER-KOVÁCS et al (2013). Confi rming our fi ndings, they observed a decreasing diversity in diatom assemblages parallel to increasing salinity/conductivity, and/or nutrient (especially phosphate) contents.…”
Section: Changes In Evennesssupporting
confidence: 88%
“…The best indicator species for high nutrient levels or pollution were as follows: N. palea, N. trivialis, and L goeppertiana in spring; E. minima and Gomphonema angustum in summer; E. minima and N. frustulum in autumn; and E. minima in winter. These results confirmed that N. palea is cosmopolitan and a pollution-tolerant species, and it was dominant in polluted rivers in Spain (Urrea and Sabater 2009), Kenya (Ndiritu et al 2006), Vietnam (Duong et al 2006), and Brazil (Bere and Tundisi 2011). E. minima, a small cell-sized diatom, can adapt to different conditions (Raven 1998), and it was the dominant taxon at polluted sites after the summer due to harsh conditions such as flooding and excess light.…”
Section: Discussionsupporting
confidence: 59%
“…It may be related to the hydrological characteristics of the Ganhe River, which experiences a wet season in summer (Yang et al 2009). Biodiversity indices (e.g., diversity, species richness, and evenness) are not always predictable in response to environmental conditions (Ndiritu et al 2006). We found that the diversity was higher in the urbanized area with an intensity of anthropogenic disturbance, with lower values in the upper reaches of the lower trophic level.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Pan et al, 1999;Soininen et al, 2004;Kelly et al, 1995;Rott et al, 1997Rott et al, , 1999Coring, 1999) and have been widely related to specific environmental conditions in different geographical regions (Soininen, 2002;Martinez de Fabricius et al, 2003;Ndiritu et al, 2006, Gomez & Licursi, 2001, Lobo et al, 20022004a,b). Consequently, several studies have addressed the tolerances and preferences of diatoms along a number of environmental gradients, such as gradients in salinity, pH, trophy, saprobity and current preference (e.g.…”
Section: Introductionmentioning
confidence: 99%